Towards the creation of a unified glossary of Russian biobanks - A. A. Mikhailova; Yu. A. Nasykhova; A. I. Muravyov; A. Yu. Efimenko; A. S. Glotov (Кардиоваскулярная терапия и профилактика, 2020)
To carry out research projects, clinical trials and other studies in the field of personalized medicine, it is necessary to have collections of high-quality biological samples of various types. With the development of biomedical technologies, the need for large collections of biological samples will grow every year, which necessitates the creation of various biobanks for standardized collection, storage and distribution of such samples. One of the goals of the National Association of Biobanks and Biobanking Specialists is the development of a network of Russian biobanks interacting with each other at various levels, as well as the development and implementation of organizational and legal tools for its regulation. It is required not only to standardize the access and exchange of biological samples and data, but also to create a unified terminology that will be used by biobanks throughout Russia. The main aim is to create an accurate, professional and legally correct tool containing information accessible and understandable to a wide range of researchers.